Learning from farmers on potentials and limits for an agroecological transition: a participatory action research in Western Sicily - Conte, Luigi; Prakofjewa, Julia; Floridia, Tiziana; Stocco, Alice; Comar, Vito; Gonella, Francesco; Lo Cascio, Martina (Frontiers in Environmental Science, 2024)
Like many Mediterranean areas, the Italian island of Sicily is facing multiple environmental pressures such as soil loss, fire hazards, and extreme meteorological events with negative impacts on local food systems. In response to these threats, a re-thinking of local agriculture and natural resource management is becoming increasingly needed. Agroecology is known as a robust proposal for building more resilient food systems grounded in farmers' knowledge and practices. Nevertheless, agroecological farming experiences struggle to operate and survive in Sicily because of unfavorable political-cultural, environmental, and socio-economic conditions. Learning from small-scale farmers about the ways they perceive, understand and overcome structural limits and environmental constraints is key for a transition to agroecology in the study area. Understanding its potentials and limits is essential for planning and identifying transformative actions. We approached the problem by adopting a participatory action research methodology involving selected groups of farmers in Western Sicily. We applied a co-creative approach and developed a systemic analysis of the socio-ecological narratives to identify possible leverage points for a transition to agroecology in the study area. We identified a local potential for shifting the actual system of water and fire hazards management to new systems of participative land stewardship. To be effective these should be designed to support agroecological farmers' income by shifting social practices related to food, and by reducing the influence of dominant agribusiness actors. These can be achieved by implementing solutions based on circulation of local ecological knowledge within systems of participatory guarantee designed to favor the development of solidarity economies and mutualistic relations between farmers, scientists, and communities. Our work suggests that scientists’ facilitation and knowledge co-creation might be of key importance to structure local, more sustainable food systems.